2021
DOI: 10.1017/s136898002100029x
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation and risk for congenital hydrocephalus in China

Abstract: Objective: We examined whether folic acid (FA) supplementation prevented congenital hydrocephalus (CH) in more than 200,000 births in China. Design: A large population-based cohort study. Setting: All births at 20 complete gestational weeks, including live births, stillbirths, and pregnancy terminations, and all structural birth defects regardless of gestational week were recorded. The prevalence of births with CH was classified by maternal characteristics and FA supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…While prioritizing IDA among pregnant women, attention should also be paid to other causes of anemia. The nutritional status of FA among pregnant women has remarkably improved after the national FA supplementation program for preventing neural tube defects took effect in 2009 [ 88 ]. Nonetheless, one cross-sectional study conducted in northwestern China showed that about 12.1% of women in late pregnancy were deficient in FA, and 69.6% of the women were deficient in vitamin B12 [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…While prioritizing IDA among pregnant women, attention should also be paid to other causes of anemia. The nutritional status of FA among pregnant women has remarkably improved after the national FA supplementation program for preventing neural tube defects took effect in 2009 [ 88 ]. Nonetheless, one cross-sectional study conducted in northwestern China showed that about 12.1% of women in late pregnancy were deficient in FA, and 69.6% of the women were deficient in vitamin B12 [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of anorectal malformation is thought to be multifactorial and therefore both genetics and environmental factors, such as tobacco, caffeine, and alcohol, are likely involved in its development [ 6 ]. On the contrary, folic acid supplementation has been reported to reduce the risk of occurrence of anorectal malformations [ 7 , 8 ]. These lesions can be diagnosed prenatally by MRI, ultrasonography, and examination at the time of birth [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that supplement of trace elements is one of the most sustainable, safe, effective means to prevent offspring from CH during pregnancy. A large population-based cohort study demonstrated that folic acid supplementation can notably attenuate the incidence of CH, especially in cold areas at high latitudes (OR 0.29, 95% CI 0.12-0.69) [62] (Table 1).…”
Section: Congenital Hydrocephalusmentioning
confidence: 99%